Populist discourse and entrepreneurship: The role of political ideology and institutions - Bennett, Daniel L.; Boudreaux, Christopher; Nikolaev, Boris (Journal of International Business Studies, 2023)
Abstract Using institutional economic theory as our guiding framework, we develop a model to describe how populist discourse by a nation’s political leader influences entrepreneurship. We hypothesize that populist discourse reduces entrepreneurship by creating regime uncertainty concerning the future stability of the institutional environment, resulting in entrepreneurs anticipating higher future transaction costs. Our model highlights two important factors that moderate the relationship. First is the strength of political checks and balances, which we hypothesize weakens the negative relationship between populist discourse and entrepreneurship by providing entrepreneurs with greater confidence that the actions of a populist will be constrained. Second, the political ideology of the leader moderates the relationship between populist discourse and entrepreneurship. The anti-capitalistic rhetoric of left-wing populism will create greater regime uncertainty than right-wing populism, which is often accompanied by rhetoric critical of free trade and foreigners, but also supportive of business interests. The effect of centrist populism, which is often accompanied by a mix of contradictory and often moderate ideas that make it difficult to discern future transaction costs, will have a weaker negative effect on entrepreneurship than either left-wing or right-wing populism. We empirically test our model using a multi-level design and a dataset comprised of more than 780,000 individuals in 33 countries over the period 2002–2016. Our analysis largely supports our theory regarding the moderating role of ideology. However, surprisingly, our findings suggest that the negative effect of populism on entrepreneurship is greater in nations with stronger checks and balances.